Correction of Mandibular Prognathism by Orthognathic Surgery in a Patient with Acromegaly: - Gharnizadeh, Kamal; Mohammadi, Alireza; Malekpoor, Zahra; Sohrabi, Maryam (Galen Medical Journal, 2013)
Background: Acromegaly, a condition which is associated with an acquired progressive disfigurement mainly involving the face and extremities, is a clinical syndrome which results from excessive production of growth hormone (GH) most commonly due to adenoma of the pituitary gland. Acromegaly is a rare disease which due to its slow progression, is mostly diagnosed in late adulthood. Bilateral symmetrical prognathic mandible is considered as a diagnostic symptom of acromegaly. Nowadays, orthognathic surgery is done for treatment of this skeletal deformity; however, because of its relapse after surgery, the efficacy of this procedure remains uncertain. Case report: In this report we present a 33 years old man who was admitted for correction of Prognathism resulted from acromegaly in Bou-Ali Hospital. Class III skeletal growth form was achieved in his cephalometry analysis. Macroglossia, concave profile with prominent supra orbital ridges, prognathism, large lips and bulbous nose were detected in his physical examination. Orthognathic surgery as well as median glossectomy was performed and after 1 year follow up no recurrence was detected. Conclusion: It is assumed that keeping GH in a normal range before the surgery and also evaluation of orthognathic aspect and endocrine status of the patient in the follow ups are effective in preservation of orthognathic surgery outcomes.